Relationship of Smartphone Addiction and Self-Efficacy with Academic Achievement in Adolescents - Agesti, Linda Pradani; Fitryasari, Rizki; Armini, NK Alit; Yusuf, Ah (Universitas Airlangga, 2019)
Introduction: Adolescents have a greater interest in smartphone use, this makes teens more vulnerable to experiencing smartphone addiction. Academic achievement in Indonesia is still relatively low, this is influenced by several factors, internal factor like self-efficacy and the external factor includes are smartphone use. The purpose of this study was to analyze the relationship between smartphone addiction and self-efficacy with academic achievement based on Bandura's theory.Method: The number of samples was 219 students by using cluster sampling. The independent variable is smartphone addiction and self-efficacy. The dependent variable is academic achievement. Data were collected using questionnaires and analysis with the Spearman test α <0.05.Result: Smartphone addiction can reduce self-efficacy (p = 0,009) direction of correlation negative (r = -0,177). Smartphone addiction can also reduce academic achievement (p = 0.046) direction of correlation negative (r = -0.135). Self-efficacy has no relationship with academic achievement (p = 0.262).Conclusion: Smartphone addiction can make teenagers experience restlessness when not using a smartphone, while self-efficacy can be influenced by anxious and restless behavior. Nurses need to do health education for parents and students related to smartphone addiction and its relationship with student self-efficacy and academic achievement.